PENGUATAN KELEMBAGAAN GOTONG ROYONG DALAM PERSPEKTIF SOSIO BUDAYA BANGSA : Suatu Upaya Revitalisasi Adat Istiadat dalam Penyelenggaraan Pemerintahan (Forum Penelitian Agro Ekonomi, 2016)
Gotong royong is social capital found in most of Indonesian sub-cultures. In gotong royong instituion we find social values, collective spirit, mutual collective trust, and organization aimed at common progress. Roles of gotong royong are significant in alleviating Indonesian from undeveloped economy of basic needs and foreign dominance. Gotong royong institution revitalization is necessary to involve people through deep participation in order to implement good governance. Upper aspect of gotong royong is norms. It is possible to improve social structure through gotong royong both at local and national levels. Collective, focused movement of this institution enables the government to establish self-reliance society based on social justice. Therefore it needs political will from all stakeholders both at regional and central levels.
Keywords: custom revitalization; gotong royong institution; society; government; people progress; revitalisasi adat-istiadat; kelembagaan gotong royong; masyarakat; pemerintahan; kemajuan bangsa